2019
DOI: 10.1016/j.commatsci.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Combined molecular dynamics and phase-field modelling of crack propagation in defective graphene

Abstract: In this work, a combined modelling approach for crack propagation in defective graphene is presented. Molecular dynamics (MD) simulations are used to obtain material parameters (Young's modulus and Poisson ratio) and to determine the energy contributions during the crack evolution. The elastic properties are then applied in phase-field continuum simulations which are based on the Griffith energy criterion for fracture. In particular, the influence of point defects on elastic properties and the fracture toughne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…In the proposed model, the interface formally has the same number of material parameters as the surrounding bulk material. In earlier investigations with the model [17,36], only elastically homogeneous cases were investigated. The elastic constants of the two bulk materials were also applied within the interface even if it was in principle possible to consider completely different elastic constants, in a similar fashion as in Equation ( 24).…”
Section: Incorporation Of Elastic Heterogeneities Near the Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In the proposed model, the interface formally has the same number of material parameters as the surrounding bulk material. In earlier investigations with the model [17,36], only elastically homogeneous cases were investigated. The elastic constants of the two bulk materials were also applied within the interface even if it was in principle possible to consider completely different elastic constants, in a similar fashion as in Equation ( 24).…”
Section: Incorporation Of Elastic Heterogeneities Near the Interfacementioning
confidence: 99%
“…In other words, assuming an interface crack, the actual interface fracture toughness G i,act c for the one-dimensional example is not equal to the specified interface fracture toughness G i c in Figure 4a. After some straightforward manipulation of Equation (35), which describes the total crack energy, and making use the analytical solution (36), one obtains…”
Section: One-dimensional Phase-field Profiles At Interfacesmentioning
confidence: 99%
“…In these nano-composite studies, graphene has proven to be an extraordinary reinforcing candidate for the matrices, wherein fracture of graphene is investigated in detailed. Moreover, Hansen-Dörr et al [127] reported the effect of point defects in graphene on the critical stress intensity factor and elastic properties using MD simulations.…”
Section: Brittle Materials—advances In Fracture Study At Nanoscalementioning
confidence: 99%
“…In the proposed model, the interface formally has the same number of material parameters as the surrounding bulk material. In earlier investigations with the model [16,35], only elastically homogeneous cases were investigated. The elastic constants of the two bulk materials were also applied within the interface even if it was in principle possible to consider completely different elastic constants, in a similar fashion as in Equation (26).…”
Section: Incorporation Of Elastic Heterogeneities Near the Interfacementioning
confidence: 99%